Efektivitas Problem Based Learning dalam Meningkatkan Kemampuan Literasi Numerasi pada Materi Kalor dan Perpindahannya: The Effectiveness of Problem Based Learning in Improving Numeracy Literacy Skills in Heat and Its Movement Materials - Maydina Sannyya Qonita; Woro Setyarsih (Pendidikan Fisika Universitas Nurul Huda, 2026)
The low level of numeracy literacy among Indonesian students, as reflected in the 2022 PISA report, calls for innovative learning strategies that can improve scientific concept understanding. This study aims to explore the effectiveness of the Problem-Based Learning (PBL) model in enhancing numeracy literacy skills among high school students on the topic of heat and its transfer. The method used was a quasi-experimental design with a one-group pretest-posttest design involving two classes with 35 and 36 students each, consisting of an experimental class and a replication class. Data were collected through pre-tests and post-tests using a numeracy literacy test instrument analyzed based on numeracy literacy indicators with the assistance of SPSS statistics software. The results of the study showed a significant increase in numeracy skills, with the average post-test score reaching the proficient category and a shift in the distribution of competency levels from basic to proficient. These findings confirm that PBL is effective in honing students' numeracy literacy skills, including the application of symbols, visual data analysis, and evidence-based reasoning, thereby supporting the requirements of the Merdeka Curriculum